MANAGEMENT OF INTELLECTUAL INTELLECTUAL (IQ) EMOTIONAL INTELLIGENCE (EQ) AND SPIRITUAL INTELLIGENCE (SQ) IN LEARNING - Nurlaili Hidayatul Baiti (IAI AGUS SALIM METRO LAMPUNG, 2022)
Basically, humans were created with the elements of intelligence. The learning objectives will work well, if educators can apply an intelligence either IQ, EQ, SQ from Allah SWT as a potential for humans that must be played in a balanced manner, but the fact that so far this intelligence is only dominated by IQ, without having to initiate or involve other intelligences EQ, SQ as an intelligence that really provides a great opportunity to be successful in society and the world of education, of course, because emotional intelligence is according to the results and research of psychologists and practitioners, they undergo and exemplify people who aresuccessful in the world of work, it turns out not only seen only IQ abilities, and an educator must be able to control his emotions and feelings with others, when empathizing and socializing, communicating, humanist so that he can take a lesson learned and meaningful in attitudes and actions. The main focus of learning is the potential that is in students who must be guided and developed into a smart person in facing and fulfilling the needs of their life, therefore learning must be done in order to balance the personal potential of students including IQ EQ SQ according to the circumstances / problems Learning objectives will work well if educators apply a good intelligence IQ EQ SQ as potential for humans. This study aims to describe good intelligence, IQ, EQ, SQ, as a potential for humans to learn. The difference between each intelligence. The data collection techniques used were documentation, tests, literature study. The research subjects were students, and the research used a qualitative approach. humanist so that he can take a lesson learned and meaningful in attitudes and actions. The main focus of learning is the potential that is in students who must be guided and developed into a smart person in facing and fulfilling the needs of their life, therefore learning must be done in order to balance the personal potential of students including IQ EQ SQ according to the circumstances / problems Learning objectives will work well if educators apply a good intelligence IQ EQ SQ as potential for humans.